(NmUZYKAL_NO(B-(NKRITI^ESKIE STAT_I(B.s (NISTORIQs - (Np(B.(Ni(B.(N~AJKOWSKIJs; (Na(B.(Na(B.(N}ERBAKOWAs (NREDAKTORs ((NlENINGRADs (NmUZYKAs, 1986)
(Nw KNIGE SOBRANY STATY I RECENZII WELIKOGO RUSSKOGO KOMPOZITORA(B.s
Keywords: (NISTORIQs